Memory Similarities Between Essential Tremor and Parkinson’s Disease: A Final Common Pathway? - Lafo, Jacob A. (Clin Neuropsychol, 2015)
OBJECTIVE: A growing body of literature supports the view that essential tremor (ET) involves alteration of cerebellar-thalamo-cortical networks which can result in working memory and executive deficits. In this study we tested the hypothesis that individuals with ET would exhibit worse performance on memory tasks requiring more intrinsic organization and structuring (i.e., word lists) relative to those with fewer ‘executive’ demands (i.e., stories), similar to that previously observed in individuals with Parkinson’s disease (PD). METHOD: Participants included a convenience sample of 68 ET patients and 68 idiopathic PD patients, retrospectively matched based on age, education, and sex. All patients underwent routine neuropsychological evaluation assessing recent memory, auditory attention/working memory, language, and executive function. Memory measures included the Hopkins Verbal Learning Test-R and WMS-III Logical Memory. RESULTS: Both ET and PD patients performed significantly worse on word list than story memory recall tasks. The magnitude of the difference between these two memory tasks was similar for ET and PD patients. In both patient groups, performance on measures of executive function and auditory attention/working memory was not distinctly correlated with word list vs. story recall. CONCLUSIONS: These findings suggest that frontal-executive dysfunction in both ET and PD may negatively influence performance on memory tests that are not inherently organized. Although the pathophysiology of these two ‘movement disorders’ are quite distinct, both have downstream effects on thalamo-frontal circuitry which may provide a common pathway for a similar memory phenotype. Findings are discussed in terms of neuroimaging evidence, conceptual models, and best practice.